Distinct epigenetic and gene expression changes in rat hippocampal neurons after Morris water maze training - Carter, Sylvia D.; Mifsud, Karen R.; Reul, Johannes M. H. M. (Frontiers in Behavioral Neuroscience, 2015)
Gene transcription and translation in the hippocampus is of critical importance in hippocampus-dependent memory formation, including during Morris water maze (MWM) learning. Previous work using gene deletion models has shown that the immediate-early genes (IEGs) c-Fos, Egr-1 and Arc are crucial for such learning. Recently, we reported that induction of IEGs in sparse dentate gyrus neurons requires ERK MAPK signaling and downstream formation of a distinct epigenetic histone mark (i.e. phospho-acetylated histone H3). Until now, this signaling, epigenetic and gene transcriptional pathway has not been comprehensively studied in the MWM model. Therefore, we conducted a detailed study of the phosphorylation of ERK1/2 and serine10 in histone H3 (H3S10p) and induction of IEGs in the hippocampus of MWM trained rats and matched controls. MWM training evoked consecutive waves of ERK1/2 phosphorylation and H3S10 phosphorylation, as well as c-Fos, Egr-1 and Arc induction in sparse hippocampal neurons. The observed effects were most pronounced in the dentate gyrus. A positive correlation was found between the average latency to find the platform and the number of H3S10p-positive dentate gyrus neurons. Furthermore, chromatin immuno-precipitation (ChIP) revealed a significantly increased association of phospho-acetylated histone H3 (H3K9ac-S10p) with the gene promoters of c-Fos and Egr-1, but not Arc, after MWM exposure compared with controls. Surprisingly, however, we found very little difference between IEG responses (regarding both protein and mRNA) in MWM-trained rats compared with matched swim controls. We conclude that exposure to the water maze evokes ERK MAPK activation, distinct epigenetic changes and IEG induction predominantly in sparse dentate gyrus neurons. It appears, however, that a specific role for IEGs in the learning aspect of MWM training may become apparent in downstream AP-1- and Egr-1-regulated (second wave) genes and Arc-dependent effector mechanisms.